Laparoscopic radical prostatectomy: transfer validity - Erdogru, Tibet; Yucel, Selcuk; Frede, Thomas; Baykara, Mehmet; Rassweiler, Jens; Teber, Dogu (International journal of urology, 2010)
Objectives: The impact of a formal fellowship training program on the independent practice of the trainees (i.e. transfer validity) has not been evaluated. We analyzed the transfer validity of a structured curriculum in an in-door as well as an out-door setting. Methods: After completing their training, two fourth generation laparoscopic surgeons who started at the same time compared operative parameters and oncological outcomes in their independent practice, prospectively analyzing the next 100 patients in each. One surgeon continued laparoscopic radical prostatectomy (LRP) in the same center of excellence (Group-In), whereas the other implemented the procedure in a separate academic center (Group-Out). Results: The demographics for both groups (Group-In vs Group-Out) were similar regarding age, prostate volume and preoperative prostate-specific antigen levels. Mean operation times (214.8 vs 224.2 min; P = 0.494) and estimated blood loss (472.4 vs 402.6 mL; P = 0.109) did not differ significantly in both groups as well as complication rate (20 vs 24%), median catheter time (8 vs 8.5 days) and continence rates at 12 months (95 vs 95.5%). According to the pathological stages, the rates of positive surgical margins were similar for pT2 (3.2 vs 4.3%) and pT3 (42.8 vs 45.2%), respectively. Conclusions: With a well designed, long-term preclinical and clinical fellowship training program, LRP techniques can be efficiently transferred from the center of excellence to other centers with no significant impact on surgical, functional and oncological outcomes.
Gesehen am 20.03.2023